FGF18 induces chondrogenesis and anti-osteoarthritic effects in a mouse model for TMJ degeneration - Flavia Gomes Velasque Gama; Christina Casciani; Eliane Hermes Dutra (PLoS ONE, 2025)
Objective Temporomandibular Joint Osteoarthritis (TMJ-OA) is a degenerative disease characterized by progressive loss of cartilage and subchondral bone sclerosis. Currently there are no effective treatments for TMJ-OA. FGF18 is a member of the fibroblast growth factor family with essential roles for chondrogenesis, selectively binding to FGFR3 receptor. Studies have reported FGF18 attenuates cartilage degradation. Whereas the anti-osteoarthritic effects of FGF18 in the articular cartilage are known, the effects of FGF18 in a TMJ fibrocartilage degeneration mouse model remain to be determined. The goal of this project was to determine the effects of intra-articular injections of FGF18 in a mouse model for TMJ degeneration. Method Prosthesis tubes were bonded at the left lower incisor of 6-week-old triple collagen transgenic mice (Col1a1XCol2a1XCol10a1), creating unilateral crossbite and degeneration of the TMJ fibrocartilage. Six weeks after placement of prosthesis tubes, experimental and control mice received intra-articular injections of rmFGF18 (5µg/week) or saline, respectively, for 3 weeks. Results Mice receiving saline intra-articular injections presented with a thinner cartilage layer with decreased proteoglycan distribution and Edu positive cells (chondrocyte proliferation marker), while mice injected with rmFGF18 presented with significant increased fibrocartilage thickness, remarkable proteoglycan distribution and chondrocyte proliferation, suggesting healing of the induced degeneration. Furthermore, reversal of the TMJ degeneration achieved by rmFGF18 injection was accompanied by a substantial reduction in Noggin (antagonist of BMP signaling), increase in TIMP1 (inhibitor of metalloproteinases such as MMP13) and decrease in MMP13 expression. Conclusion Our results postulate FGF18 as a powerful growth factor for the healing of TMJ fibrocartilage.